World Bank Group Support for Innovation and Entrepreneurship: An Independent Evaluation (World Bank, 2015)
In economic growth the largest differences between developed and developing economies are in innovation performances. Innovation is critical for growth, but it is increasingly important for addressing major development changes, such as those related to inclusion and sustainability. Recognizing this pattern, many countries are promoting innovation and entrepreneurship. Market and government failures and other bottlenecks impede innovation and entrepreneurship, particularly in developing countries. These countries need to build the capacity to find, absorb, and use new technologies and processes as well as foster entrepreneurs who can take risks, look for finance, and bring new products and processes to market. The Independent Evaluation Group reviewed the investment portfolio in innovation and entrepreneurship interventions over the past decade across the World Bank Group. IEG found that this investment is substantial, but its effectiveness can be enhanced through broad, systemic efforts. Urgent action is required to enhance coordination, consultation, and linkages on innovation and entrepreneurship initiatives across networks, sectors, and regions. Another challenge is to develop practical solutions for people who earn less than $2 a day?an issue relevant to middle-income as well as low-income countries. Sustained efforts are required to identify different mechanisms and implementation arrangements that are effective and efficient. Monitoring and evaluation is also important for scale-up of promising interventions and mechanisms to effectively capture and share knowledge within and across the Bank Group. IEG presented a number of recommendations to strengthen the effectiveness of Bank Group support for innovation and entrepreneurship. They involved implementing a strategic framework that considers the new World Bank Group strategy and provides building blocks, examining alternative approaches for financing early-stage start-ups, and promoting knowledge sharing within the Bank Group in numerous ways. Both development and business audiences will be interested in this evaluation: the lessons distilled and examples highlighted can be applied in many business contexts.